The Utilization of Feather Meal Fermented Using Bacillus sp. From Tiger Shrimp (Penaeus monodon) For Fish Feed of Barramundi (Lates calcarifer, Bloch) Fingerling - Citra Panjaitan; Adelina '; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted on 1 May-1 July 2017. The purpose of this study toevaluated the uses of feather meal fermented in fish feed and to determine thenumber of feather meal fermented in fish feed formulation of barramundi (Latescalcarifer, Bloch), the effect on digestibility, growth, feed efficiency and proteinretention. This study uses a completely randomized design (RAL) with one factor,the level 5 treatment and 3 replications. Treatments with feather mealfermentation, P0 (0%), P1 (5%), P2 (10%), P3 (15%), P4 (20%). Feed proteincontent of 47,52%. The result show that the highest treatment contained in P2.Use feather meal fermented formulated in the feed as much as 10%, produces thebest barramundi fish seed growth is digestibility of the feed 65,16%, digestibilityof protein 48,75%, the feed efficiency of 26,33%, retention of protein 41,67% andspecific growth rate of 1,71%.Keyword: feather meal, Bacillus sp., fermented, barramundi (Lates calcarifer,Bloch), fish feed